2022
DOI: 10.1177/14680874221105161
|View full text |Cite
|
Sign up to set email alerts
|

Mixing controlled compression ignition with methanol: An experimental study of injection and EGR strategy

Abstract: Methanol is a fuel that can be produced using renewable electricity, green hydrogen, and a carbon-neutral carbon source. As a low-carbon liquid fuel, methanol is a leading candidate as a drop-in replacement fuel for rapid decarbonization of the transportation sector. In this work, methanol is tested experimentally in mixing-controlled compression ignition using a single-cylinder research engine. Specifically, the impact of a double injection strategy and high exhaust gas recirculation (EGR) dilution on perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The ECU used in the experiment was manufactured by BOSCH, model ME788. The Methanol flow control unit (13) controlled the flow of methanol into the methanol dissociating device (1) based on engine information provided by ECU (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ECU used in the experiment was manufactured by BOSCH, model ME788. The Methanol flow control unit (13) controlled the flow of methanol into the methanol dissociating device (1) based on engine information provided by ECU (14).…”
Section: Methodsmentioning
confidence: 99%
“…Methanol, with a hydrogen mass fraction of 12.5%, is also considered a promising liquid hydrogen carrier due to its ability to conveniently and efficiently produce hydrogen through methods such as dissociating or reforming. 13 Hydrogen has a very high flame speed. 14 Adding hydrogen to the engine can shorten the flame development period, leading to earlier heat release.…”
Section: Introductionmentioning
confidence: 99%
“…Gainey et al [93] conducted experiments with methanol CI utilizing EGR on a 0.423 L single-cylinder research engine at medium to high loads, employing a standard diesel CR of 16. Their findings indicated a decrease in engine-out NO x emissions with increasing EGR, accompanied by an elongation of the heat release and a slight reduction in efficiency.…”
Section: Egrmentioning
confidence: 99%
“…One possibility is employing a pilot injection alongside a larger main injection to spread out the cooling effect induced by methanol injection while utilizing the pilot as a means to preheat the combustion chamber, thereby facilitating the ignition of the main injection. Gainey et al [93] demonstrated that advancing both the pilot and main injections could positively influence efficiency, provided that excessive fuel does not combust before TDC. Additionally, they highlighted the significance of pilot size, emphasizing that an insufficiently sized pilot might fail to adequately assist the main injection in ignition.…”
Section: Pilot Injectionmentioning
confidence: 99%